Role of oxidative stress in facilitating carcinogenesis - Natarajan, Venkateswaran (International Journal of Research in Medical Sciences, 2017)
The carcinogenic role of ROS has been a great debate in the past and will be in the future. ROS is produced by both internal (inflammation) and external sources (UV). ROS is important for various important signalling mechanisms for the normal cellular survival. Even though literature exists to support the role of ROS in cancer, the magnitude of its expression and cell type it is expressed will determine whether it plays a positive (apoptosis) or negative role (genomic instability) in cancer. Apart from inducing DNA damage, ROS facilitates carcinogenesis by regulating cell cycle progression, gap junction, inflammation etc. The present review updates the recent discoveries of how ROS regulates these important cellular signalling mechanisms to facilitate carcinogenesis.